2010 11th International Thermal, Mechanical &Amp; Multi-Physics Simulation, and Experiments in Microelectronics and Microsystem 2010
DOI: 10.1109/esime.2010.5464550
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element modelling of adhesion phenomena in MEMS

Abstract: In the last years many research works were focused on adhesion in micro-electro-mechanical systems (MEMS). In fact, that phenomenon can endanger the reliability of MEMS, both during the fabrication phase and in the operation conditions. The aim of the present study is to simulate the adhesion phenomena in different environmental conditions, by using Finite Element (FE) computational simulations on a representative part of the surface. A significant part of the work is devoted to the proper generation of FE mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…As for the silicon-gold contact model, the main parameters are listed in Table 1 [15,27], and the thickness of Au layer is 40 nm. Thus, the equivalent curvature radius is 1515 nm and the equivalent elastic module is 56.02 Gpa.…”
Section: Model Of Contacting Areamentioning
confidence: 99%
See 1 more Smart Citation
“…As for the silicon-gold contact model, the main parameters are listed in Table 1 [15,27], and the thickness of Au layer is 40 nm. Thus, the equivalent curvature radius is 1515 nm and the equivalent elastic module is 56.02 Gpa.…”
Section: Model Of Contacting Areamentioning
confidence: 99%
“…Pennec et al indicated the dependence of contact characteristics on the surface roughness [14]. Ardito et al concentrated mainly on the surface contact phenomenon of MEMS devices and finished the corresponding physical model under different environmental conditions [15]. Cui et al established a multi-scale model of rough surface contact and calculated the deformation level of the surface under pressure [16].…”
Section: Introductionmentioning
confidence: 99%
“…They assumed a constant adhesive force between the contacting surfaces, which is not always rigorous and has less physical basis. For completeness, another approach is to consider finite element simulations of a reduced number of interacting asperities combined with capillary and van der Waals forces interactions, [29].…”
Section: Introductionmentioning
confidence: 99%
“…The generalization to two rough surfaces can be conducted by finite element simulations where the surfaces are discretized, as it has been proposed for elastoplastic asperities by Pei et al [34] without accounting for adhesion, or by Ardito et al [35] with capillary and VDW effects. The treatment of rough surfaces can also be obtained from the single asperity study, by extending the GW-elastic formulation and by using the CEB single asperity model, [20].…”
Section: Introductionmentioning
confidence: 99%